Investigação do efeito anti-inflamatório do alcaloide sintético tetrahidroisoquinolinico, o 2, 6-dimetoxi-4-(7-metoxi-1,2,3,4-tetra-hidroisoquinolin-1-il) fenol (Di-MTF), em modelos animais de inflamação aguda e estudo in silico - Vieira, Cosmo Isaias Duvirgens (2023)
Inflammation is a physiological process triggered by cells and molecules of local action capable of dissipating the infectious/aggressor process and restoring homeostasis. However, if it becomes persistent and long-lasting, it evolves into a chronic state such as acute lung injury (ALI), affecting the alveoli, with cell infiltration, damage to the alveolar-capillary barrier and production of cytokines. The mortality rate of this disease is 40%-60% with ineffective pharmacological control. Therefore, the aim of this study was to investigate the anti-inflammatory effect of the tetrahydroisoquinoline alkaloid, Di-MTF in experimental models of acute inflammation and in silico studies. For this purpose, Swiss female mice were pre-treated with Di-MTF (0.6; 1.25; 2.5mg/kg, orally) and challenged, on the foot pad, with carrageenan (CG), prostaglandin (PGE2), bradykinin (BK), 5 hydroxytryptamine (5HT), compound 48/80 or histamine to assess anti-edematogenic activity and, with intraperitoneally administered GC, assess permeability, total and differential cell migration, and cytokines. To assess acute lung injury, BALB/c mice were challenged with lipopolysaccharide (LPS) and treated with Di-MTF(1.25mg/kg). Twenty-four hours after the challenge, the animals were euthanized, and bronchoalveolar lavage (BALF), blood and lungs were collected for cellular and molecular analyses. For the prediction of molecular targets and pharmacokinetic and pharmacodynamic profile, in silico studies were performed using ADMET software (absorption, distribution, metabolism and toxicity), HyperChem and Molegro Virtual Docker (MVD). Pre-treatment with Di-MTF reduced (p<0.05) paw edema, migration of neutrophils to the peritoneum, peritoneal extravasation of proteins and reduction of pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α). In experimental ALI, Di-MTF reduced (p<0.05) the migration of leukocytes to the lung, mainly neutrophils, protein fluids, pulmonary edema, and cytokines, IL-1β, IL-6 and TNF-α, the IL-6 and TNF-α were reduced at the systemic level. Histological lesions of lung tissue were attenuated with treatment, such as cell infiltrates, edema, and hemorrhage. In silico molecular docking studies showed that Di-MTF showed better interaction with p38 MAPK and Toll-like 4 (TLR4), binding energies of -66.680 kcal/mol and -37.577 kcal/mol, respectively. Its ADMET parameters were acceptable, showing safety and bioavailability. Therefore, we conclude that Di-MTF exerted an anti-inflammatory effect by modulating inflammatory parameters linked to the interruption of Toll-like 4 (TLR4) signaling pathways, p38MAPK. The molecule proved to be safe with good bioavailability, being a possible pharmacological tool for the treatment of acute inflammation.